Implementasi Media Snakes-Ladders dalam Penguasaan Mufradat di MTs Assunniyyah Jember - Zainuri Zainuri; Nurma Kholifatul Hafidah (INAIFAS Press, 2022)
Teachers must be able to present Arabic learning with the media well, so students can understand lessons easily. This article discusses the snakes-ladders media which is applied in learning Arabic on yaumiyyatunā material. This research oriented to check the mastery of Arabic mufradāt through snakes-ladders media in 8th grade students at MTs Assunniyyah Kencong Jember. This study used a qualitative approach because the object of this research focuses on the process of mastering mufradāt with snakes-ladders media. Through snakes-ladders, students could master Arabic learning related to memorizing mufradāt. With the snakes-ladders, students are more enthusiastic about learning and also pay attention to the material taught by the teacher.